PENGARUH SPIRITUAL EMOTIONAL FREEDOM TEHNIQUE (SEFT) TERHADAP KUALITAS TIDUR PENDERITA HIPERTENSI DI CILACAP SELATAN - Kasron Kasron; Susilawati susilawati (Universitas Harapan Bangsa Purwokerto, 2017)
Introduction Patients with hypertension patients can have sleep disorders such as dizziness or headache, feeling tired during the day, anxiety, decreasing concentration and irritability. This study aimed to evaluate the effect of spiritual emotional freedom tehnique (SEFT) and progressive muscle relaxation (PMR) on sleep quality in patients with hypertension in South Cilacap City. Method The research used quasi-experiment with two group pre-post test group. Respondents were patients with hypertension in South Cilacap City, with the criteria forthose who were active in health care programme, able to perform independent activities, consume of anti-hypertensive drugs, have done SEFT and PMR regularly for 7 days. the exclusion criteria was patients with impaired osteoarthritis and rheumatoid arthritis. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality twice, before and 7 days after interventions SEFT. Statistic analysis used Mann-Whitney test. 32 respondents included in the criteria. Result The quality of sleep before treatment SEFT was 7 people (43.8%) poor, 9 people (56.3%) very bad. After treatment SEFT was 4 people (25%) rather good, 12 people (75%) less good. The quality of sleep before treatment PMR was 7 people (43.8%) poor, 9 people (56.3%) very bad. After treatment PMR was 3 people (18.8%) rather good, 13 people (81.3%) less good. The analysis shown the sleep quality was difference between SEFT and PMR after intervention with p-value 0.002. Discussion The study shows there is difference between SEFT and PMR after intervention in hypertensive patients in South Cilacap. SEFT and PMR can be used to improve the sleep quality of hypertensive patients.